AKSELERASI IMPLEMENTASI KURIKULUM TINGKAT SATUAN PENDIDIKAN (KTSP) DALAM PEMBELAJARAN - Rustam Abong (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Pontianak, 2008)
Educational Unit Level Curriculum (KTSP) is the operational curriculum designed by and implemented in each educational unit. While central government provides only rules of the standard course content, the technical drafting is assigned to teachers, principals and other related institutions. Therefore, accelerating the implementation KTSP in learning must be designed interactively, and the application should be in a way